Interactive Palliative and End-of-Life Care Modules for Pediatric Residents - Mindy K. Ross; Ami Doshi; London Carrasca; Patricia Pian; JoAnne Auger; Amira Baker; James A. Proudfoot; Mark S. Pian (International Journal of Pediatrics)
Background. There is a need for increased palliative care training during pediatric residency. Objective. In this pilot study, we created a comprehensive experiential model to teach palliative care skills to pediatric residents. Our Comfort Care Modules (CCMs) address pediatric palliative care (PPC) topics of breaking bad news, dyspnea, anxiety, pain management, and the dying child. We also evaluated a scoring system and gathered qualitative data. Methods. The CCMs are part of the University of California San Diego pediatric residency’s second-year curriculum. Comparisons were made for statistical trends between residents exposed to the modules (n=15) and those not exposed (n=4). Results. Nineteen of 36 residents (52%) completed surveys to self-rate their preparedness, knowledge, and confidence about PPC before and after the intervention. Resident scores increased in all areas. All improvements reached statistical significance except confidence when breaking bad news. Overall, the resident feedback about the CCMs was positive. Conclusions. This study demonstrates that the CCMs can be performed effectively in an academic setting and can benefit residents’ self-perception of preparedness, confidence, and knowledge about pediatric palliative care. In the future, we plan to implement the modules on a larger scale. We encourage their use in interprofessional settings and across institutions.